Pengaruh Dana Transfer Ke Daerah Dan Dana Desa Terhadap Tingkat Kemiskinan Desa Dengan Pendapatan Asli Daerah Sebagai Variabel Moderasi - Hasan, Saukani; Iskandar, Dadang Ishak; Rumianti, Susti (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
Poverty is a social problem that has always been an important issue in regional development programs because it is related to people's welfare. This research was conducted to determine the magnitude of the influence of Regions' Transfer Funds and Village Funds directly on the Poverty Level as well as by moderating Local Own-source Revenue in East Java during the period 2015–2021. The research population was 29 districts in East Java Province. Data with an observation span of 7 years resulted in 203 datasets in the form of historical data on Regional Original Income, Transfer Funds to Regions, Village Funds, and Regional Expenditures, and the number of poverty figures collected from the official website of the Ministry of Finance and Indonesia's central statistical agency. The data analysis method used is the SEM-PLS analysis model. The results showed that the Village Fund variable had a positive effect on the Poverty Level, but Regions' Transfer Funds had no effect while Local Own-source Revenue did not moderate the effect of Regions' Transfer Funds and Village Funds on Poverty Levels. Keywords : Regions' Transfer Funds, Village Fund, Poverty Level, Local Own-source Revenue